Clinical translation of FLASH radiotherapy: Why and how?. (October 2019) - Bourhis, Jean; Montay-Gruel, Pierre; Gonçalves Jorge, Patrik; Bailat, Claude; Petit, Benoît; Ollivier, Jonathan; Jeanneret-Sozzi, Wendy; Ozsahin, Mahmut; Bochud, François; Moeckli, Raphaël; Germond, Jean-François; Vozenin, Marie-Catherine
Highlights: FLASH-RT a paradigm-shifting method of delivering doses within an extremely short irradiation time. FLASH-RT is a promising new tool to enhance the differential effect between tumors and normal tissues. The consistency of the preclinical data clinical justifies transfer of FLASH-RT. The most relevant parameters for FLASH are the combination of dose, dose-rate within the pulse, and overall time of irradiation. A first proof of concept could be done with low-energy electrons and further tested with VHEE, protons and X-rays. Abstract: Over the past decades, technological advances have transformed radiation therapy (RT) into a precise and powerful treatment for cancer patients. Nevertheless, the treatment of radiation-resistant tumors is still restricted by the dose-limiting normal tissue complications. In this context, FLASH-RT is emerging in the field. Consisting of delivering doses within an extremely short irradiation time, FLASH-RT has been identified as a promising new tool to enhance the differential effect between tumors and normal tissues. Indeed, preclinical studies on various animal models and a veterinarian clinical trial have recently shown that compared to conventional dose-rate RT, FLASH-RT could control tumors while minimizing normal tissue toxicity. In the present review, we summarize the main data supporting the clinical translation of FLASH-RT and explore its feasibility, the key irradiation parameters and the potential technologies needed for a successful clinical translation.